Personalidad introvertida en estudiantes de educación inicial de la Facultad de Ciencias de la Educación y Humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Kling Vasquez, Vannia Fabiola (2024)
The main objective of this study is to determine the level of introverted personality among early childhood education students at the Faculty of Education and Humanities at the National University of the Peruvian Amazon in Iquitos during the year 2021. A descriptive methodology was applied, employing a field research design that was univariate and cross-sectional. The sample consisted of 194 university students who were surveyed using Google Forms and a personality inventory based on Eysenck’s theory, previously validated by experts and administered through a structured questionnaire. Results indicate that a significant majority of students (95.9%) exhibit a moderate level of introverted personality. In contrast, low (2.6%) and high (1.5%) levels of introversion are considerably less frequent, suggesting a predominance of moderate introversion within the sample studied. These findings provide a detailed understanding of the distribution of introverted personality traits within the educational context of the institution.